Association between carotid artery hemodynamics and neurovascular coupling in cerebral small vessel disease: an exploratory study - Zeng, Peng; Zeng, Bang; Wang, Xiaohua; Yin, Feiyue; Li, Binglan; Nie, Lisha; Tian, Lin; Luo, Dan; Li, Yongmei (Frontiers in Aging Neuroscience, 2025)
BackgroundRecent studies have linked disrupted cerebral hemodynamics, including pulsatility index (PI) and wall shear stress (WSS), with neuroimaging features of cerebral small vessel disease (CSVD). Cerebral neurovascular coupling (NVC) dysfunction is an important pathophysiological mechanism of CSVD. However, evidence linking the features of carotid artery hemodynamics to cerebral NVC is still lacking.ObjectiveThis study is aimed to explore the impact of PI and WSS on NVC and cognitive performance in CSVD patients using neuroimaging.MethodsThis study included 52 CSVD patients and 41 healthy controls. Carotid artery PI and WSS were measured using 4D flow magnetic resonance imaging (MRI). NVC was assessed through voxel-wise correlations between cerebral blood flow and the amplitude of low-frequency fluctuations. Multiple linear regression was used to investigate correlations between them.ResultsCSVD patients showed elevated PI in the C2 and C4 segments of the internal carotid artery and reduced WSS in the common carotid artery compared to controls. NVC measurements were significantly diminished in CSVD patients. Multiple linear regression analysis indicated significant correlations between reduced WSS and impaired NVC as well as between reduced PI and impaired NVC, but not between PI, WSS, and cognitive scores.ConclusionReduced WSS and PI in CSVD patients are associated with impaired NVC. These findings provide insights into the mechanisms underlying CSVD and suggest that hemodynamic abnormalities may serve as indicators of neurovascular dysfunction in early-stage CSVD.